EFFECT OF CORTICOSTEROID ON OCULAR TUBERCULOSIS: A SYSTEMATIC REVIEW: Poster Presentation - Observational Study - General practitioner - Rahmah Amran; dr. Dicky Stevano Zukhri, Sp.M (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objectives : There are still some disagreements between experts regarding the use of corticosteroids as an adjunctive treatment for ocular tuberculosis. Even though corticosteroid is important for controlling the inflammation to reduce further damage to the eye, some evidence claim that corticosteroid may interfere with ATT and causes more damage. This study aims to summarize and assess the role of corticosteroids on ocular tuberculosis. Methods : This study reviews papers from PubMed and Ophthalmologica Indonesiana database published in English or Indonesia between the years 2017 and 2022. The search terms used are a combination of treatment or therapy, corticosteroid, and ocular tuberculosis. Results : A total of 8 studies are included in this review with a total of 992 patients. Ocular TB can be further differentiated into anterior uveitis, intermediate uveitis, posterior uveitis, panuveitis, retinitis and retinal, vasculitis, neuroretinitis, and optic neuropathy. Corticosteroids are delivered through different routes depending on the site and severity of the inflammation. Generally, patients treated with ATT and corticosteroids have a positive response but improper timing, dosage, or route may actually worsen the infection and inflammation. Conclusion : Corticosteroids are needed as adjunctive treatment to control the inflammation from further damaging the eye. However, further studies regarding the specificity of the usage should be done as there are still limited studies about the factors affecting the outcome